Specificity of strength calculation for glued-in steel rods in LVL with unidirectional veneer - Bidakov, Andrii; Raspopov, Evhenyi; Pustovoitova, Oksana (Academic journal Industrial Machine Building Civil Engineering, 2018)
Design of joints of LVL elements with glued-in steel rods and metal connectors is considered as semi-rigid connection and requires taking of account the compliance. A comparative analysis of the test results of the beams with a metal connector and glued-in steel rods as well as solid beams is made in the paper. Design method of glued-in rods in LVL is proposed and taken into account failure mode. It allows reducing the distance between the axes of the rods as well as the distance from the rod axіs to the edges in the cross section of the beam and increasing the joint strength.
Keywords: glued-in steel rods; semi-rigid connection; laminated veneer lumber (Ultralam – R); axes and edge distance, model of rupture; two-side fixing